A federated learning approach for detecting Parkinson’s disease through privacy preserving by blockchain - Dipro, Sumit Howlader; Islam, Mynul; Nahian, Md.Abdullah Al; Azad, Moonami Sharmita (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.